IMPLEMENTATION OF THE COMPOSITION OF JUDGES IN FORESTRY CRIMINAL CASE SETTLEMENT BASED ON REGULATIONS LEGISLATION - Heri Bertus Nahak; Sudi Fahmi; Bahrun Azmi (JILPR Journal Indonesia Law and Policy Review, 2021)
Article 53 paragraph 1 has not been realized yet, the entry into force of Law Number 18 of 2013, because in the author's opinion that the government is not firm in dealing with forest destruction has not been implemented properly. After the enactment of this Law, the Chief Justice of the Supreme Court of the Republic of Indonesia must nominate candidates for ad hoc judges who are appointed through a Presidential Decree to examine cases of forest destruction. As for the formulation of the problem in this research is how the implementation of the composition of judges in the settlement of forest criminal cases based on the legislation, how the legal consequences in the implementation of the composition of judges in the settlement of forest criminal cases based on the legislation. The method used is normative legal research. Data sources consist of primary legal materials, secondary legal materials, and tertiary legal materials. In this study the data were analyzed qualitatively and in drawing conclusions the authors applied the method of deductive thinking. Based on the results of the research, it is known that the implementation of the composition of judges in the settlement of forest criminal cases based on the legislation that the existence of the composition of judges based on the legislation against the perpetrators in the law is recognized in practice.